2006
DOI: 10.1038/sj.npp.1301243
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Antagonism of Cannabinoid Effects: Differences between Marijuana Smokers and Nonmarijuana Smokers

Abstract: In non-human animals, opioid antagonists block the reinforcing and discriminative-stimulus effects of D 9 -tetrahydrocannabinol (THC), while in human marijuana smokers, naltrexone (50 mg) enhances the reinforcing and subjective effects of THC. The objective of this study was to test a lower, more opioid-selective dose of naltrexone (12 mg) in combination with THC. The influence of marijuana-use history and sex was also investigated. Naltrexone (0, 12 mg) was administered 30 min before oral THC (0-40 mg) or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 61 publications
2
86
2
Order By: Relevance
“…In rats discriminating THC, intracranial injection of the opioid peptide agonist β-endorphin or systemic administration of morphine or heroin enhanced, whereas administration of naltrexone attenuated, the discriminative stimulus effects of THC (Solinas et al 2004;; however, these interactions have not been unanimously confirmed. For example, in humans naltrexone attenuates, enhances, or has no effect the subjective and physiological effects of THC (Wachtel and de Wit 2000;Greenwald and Stitzer 2000;Haney et al 2003;Haney 2007). These inconsistencies could be related to species, drug, dose, or history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rats discriminating THC, intracranial injection of the opioid peptide agonist β-endorphin or systemic administration of morphine or heroin enhanced, whereas administration of naltrexone attenuated, the discriminative stimulus effects of THC (Solinas et al 2004;; however, these interactions have not been unanimously confirmed. For example, in humans naltrexone attenuates, enhances, or has no effect the subjective and physiological effects of THC (Wachtel and de Wit 2000;Greenwald and Stitzer 2000;Haney et al 2003;Haney 2007). These inconsistencies could be related to species, drug, dose, or history.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the μ opioid receptor agonists heroin and morphine enhanced while the opioid receptor antagonist naltrexone attenuated the discriminative stimulus effects of THC in rats . Initial reports indicated that naltrexone did not modify the subjective effects of THC in marijuana users (Wachtel and de Wit 2000;Greenwald and Stitzer 2000); however, more recent studies showed that naltrexone can increase (Haney et al 2003) or decrease (Haney 2007) the subjective effects of THC, depending on the history of marijuana use. Thus, the nature of interactions between cannabinoid and opioid receptor agonists and antagonists appears to vary markedly across conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this lack of replication may involve cannabis strength: the earlier study tested less potent cannabis (3.27% THC), producing lower ratings of 'High' and 'Good Effect' than the higher strength cannabis tested herein (5.5%). The relationship between naltrexone and cannabinoids is complex and appears to be influenced by a variety of experimental parameters including route of administration (oral THC vs smoked cannabis), THC dose, naltrexone dose, outcome measure (reinforcement vs analgesia), and cannabis use patterns (daily vs infrequent; Haney, 2007;Haney et al, 2003;Greenwald and Stitzer, 2000;Wachtel and de Wit, 2000). The underlying mechanism contributing to the variable effects observed across experimental parameters remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although pioneering studies has recently started to individuate possible useful targets for the treatment of cannabis abuse in humans (Solinas et al, 2007a;Haney et al, 2007), marijuana dependence appears difficult to treat, and its use leads to a risk of relapse as high as those found for other drugs of abuse (Stephens et al, 1994;Spear et al, 1999;Moore and Budney, 2003).…”
Section: Cannabinoids and Drug Addictionmentioning
confidence: 99%